Research on the innovation of time-honored brands from the perspective of dual ethical patterns - Ke, Di; Li, Guodong; Jiang, Yichen; Li, Yuanyuan; Liu, Yi (Frontiers in Psychology, 2023)
Innovation has become an important means to promote the high-quality development of time-honored brands. However, the research on how to stimulate innovation investment in time-honored brands, especially that conducted in the local context, is still rare. To supplement the research limitations, this study adopts the perspective of dual ethical patterns and is set in the domestic context to explore the ethical influence of traditional cultures and marketization on the innovation investment of time-honored enterprises. The results show that traditional culture and marketization level are both positively related to the innovation of time-honored brand enterprises. However, traditional culture and marketization level are mutually exclusive in their process of affecting the innovation of time-honored brand enterprises. Our study responds to the academic debate between traditional culture and the innovation of time-honored brands, while enriching the research scope on the innovation mechanism of time-honored enterprises in the local context.